1984
DOI: 10.1111/j.1600-0722.1984.tb00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of brushing technique and toothbrush design in plaque removal

Abstract: – Twenty‐four adults participated in an intraindividual crossover experimental study to compare the plaque removing ability of straight multitufted and V‐shaped brushes. Twelve of the participants had loss of periodontal tissue resulting in open but healthy interdental areas while the other 12 displayed no periodontal breakdown. In part 1 the participants were asked to brush their teeth using their own brushing technique and length over two 12‐day periods during which time they, at random, used one brush for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 15 publications
3
24
1
2
Order By: Relevance
“…The results showed statistically significant differences between the three toothbrushes. This is in contrast to the findings of the study done by Bergenholtz et al, 12 who compared a flat-trim toothbrush with V-shaped bristles and found no significant differences between the toothbrushes. In another study, Staudt et al 13 compared the efficacy of three different toothbrushes, which were convex bristle, multilevel bristle, and flat-trim bristle.…”
Section: Discussioncontrasting
confidence: 99%
“…The results showed statistically significant differences between the three toothbrushes. This is in contrast to the findings of the study done by Bergenholtz et al, 12 who compared a flat-trim toothbrush with V-shaped bristles and found no significant differences between the toothbrushes. In another study, Staudt et al 13 compared the efficacy of three different toothbrushes, which were convex bristle, multilevel bristle, and flat-trim bristle.…”
Section: Discussioncontrasting
confidence: 99%
“…The removal of plaque with the toothbrush should be complemented with suitable cleaning aids for the interproximal spaces [43,44]. Data from self-reports on oral hygiene reveal that less than 20 % of the respondents flossed [45][46][47] indicating that flossing is not very well implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies are less conclusive, as they lack control groups and standardized instructions. Furthermore, gingivitis as an indicator of habitual oral hygiene is not assessed in these studies nor are oral hygiene skills as a premise of successful hygiene [11], [12], [28], [29].…”
Section: Discussionmentioning
confidence: 99%